2012
DOI: 10.2139/ssrn.2187874
|View full text |Cite
|
Sign up to set email alerts
|

Are Groups Better Planners than Individuals? An Experimental Analysis

Abstract: Over the last ten years the literature in experimental economics has seen a growing interest in groups and how they compare to individuals in different settings. This paper contributes to the literature on this topic by investigating the comparison between groups and individuals with respect to intertemporal consumption problems. Empirical evidence has shown how dynamic optimization problems, representing intertemporal consumption decisions, involve computational difficulties that agents are not always equippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Our results are consistent with a related literature, originating with Iyengar and Lepper [ 29 ] and summarized by Chernev et al [ 30 ], showing the number of choices negatively impacts on quality of choice. It is also consistent with the literature on laboratory experiments in which individuals must make dynamic decisions in multi-period lives [ 31 34 ]. Given that less than 3% of Americans follow four major guidelines for healthy behavior [ 35 ], our general findings are consistent with empirical patterns observed in the real world.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with a related literature, originating with Iyengar and Lepper [ 29 ] and summarized by Chernev et al [ 30 ], showing the number of choices negatively impacts on quality of choice. It is also consistent with the literature on laboratory experiments in which individuals must make dynamic decisions in multi-period lives [ 31 34 ]. Given that less than 3% of Americans follow four major guidelines for healthy behavior [ 35 ], our general findings are consistent with empirical patterns observed in the real world.…”
Section: Discussionsupporting
confidence: 89%
“…Intertemporal group decision making is a relatively recent area of study [41], [42], and it is unclear if currently identified factors can explain the dynamics of project teams well.…”
Section: E Politics and Group Dynamicsmentioning
confidence: 99%